Expression of TXNIP is associated with angiogenesis and postoperative relapse of conventional renal cell carcinoma - Meszaros, Mate; Yusenko, Maria; Domonkos, Lilla; Peterfi, Lehel; Kovacs, Gyula; Banyai, Daniel (Scientific reports, 2021)
One of the common mediator of tumour progression is the oxidative stress induced by inflammatory tumour microenvironment (TME). Activated fibroblasts, local and immune cells produce reactive oxygen species (ROS) supporting tumour cell proliferation and pave the way for metastatic tumour growth. TXNIP regulates ROS generation by inhibiting the antioxidative function of thioredoxin (TXN). The shift of TXNIP/TXN balance towards overexpression of TXNIP is associated with proliferation of endothelial cells during tumor angiogenesis. The oxidative stress activates the hypoxia inducible factor-1 (HIF-1), which plays an important role in the biology of conventional RCC (cRCC). Under oxydative stress TXNIP interacts with NLRP3 inflammasome leading to maturation and secretion of inflammatory cytokine IL1 beta. To establish the role of TXNIP and downstream genes HIF1 alpha and IL1 beta in the biology of cRCC, we have applied immunohistochemistry to multi-tissue arrays containing tumours of 691 patients without detectable metastases at the time of operation. We found that cRCC displaying a fine organised capillary network with nuclear translocation of TXNIP and expressing IL1 beta have a good prognosis. In contrary, we showed a significant correlation between cytoplasmic TXNIP expression, inefficient vascularisation by unorganized and tortuous vessels causing tumour cell necrosis and postoperative tumour relapse of cRCC.